A coastal N2 fixation hotspot at the Cape Hatteras front: Elucidating spatial heterogeneity in diazotroph activity via supervised machine learning. Issue 5 (3rd April 2021) - Selden, Corday R.; Chappell, P. Dreux; Clayton, Sophie; Macías‐Tapia, Alfonso; Bernhardt, Peter W.; Mulholland, Margaret R.
Abstract: In the North Atlantic Ocean, dinitrogen (N2 ) fixation on the western continental shelf represents a significant fraction of basin‐wide nitrogen (N) inputs. However, the factors regulating coastal N2 fixation remain poorly understood, in part due to sharp physico‐chemical gradients and dynamic water mass interactions that are difficult to constrain via traditional oceanographic approaches. This study sought to characterize the spatial heterogeneity of N2 fixation on the western North Atlantic shelf, at the confluence of Mid‐ and South Atlantic Bight shelf waters and the Gulf Stream, in August 2016. Rates were quantified using the 15 N2 bubble release method and used to build empirical models of regional N2 fixation via a random forest machine learning approach. N2 fixation rates were then predicted from high‐resolution CTD and satellite data to infer the variability of its depth and surface distributions, respectively. Our findings suggest that the frontal mixing zone created conditions conducive to exceptionally high N2 fixation rates (> 100 nmol N L −1 d −1 ), which were likely driven by the haptophyte‐symbiont UCYN‐A. Above and below this hotspot, N2 fixation rates were highest on the shelf due to the high particulate N concentrations there. Conversely, specific N2 uptake rates, a biomass‐independent metric for diazotroph activity, were enhanced in the oligotrophic slope waters. Broadly, these observations suggest that N2 fixation is favored offshore but occurs continuously across the shelf. Nevertheless, our model results indicate that there is a niche for diazotrophs along the coastline as phytoplankton populations begin to decline, likely due to exhaustion of coastal nutrients.